Penanggulangan Kenakalan Remaja melalui Pendidikan Agama Islam - Yusriyah Yusriyah (Jurnal Kependidikan, 2017)
This paper is intended to describe the strategy of juvenile delinquency management through Islamic education. Islamic education, which contains a series of materials and activities, will instill positive things in students, by which juvenile delinquency is prevented. Juvenile delinquency is influenced by internal, i.e. religious education in the family, and external factors, i.e. religious education in society. Through Islamic education at school, students gain religious knowledge as self prevention from a negative influence. The activities includes stuedies with specific themes, such as fiqh for woman and other activities in ROHIS organization. Such activities can enhance faith and piety.